Analisis Kemudahan Penggunaan Kartu Digital Santri pada Koperasi Pondok Pesantren Hidayatullah Samarinda - Farhan Shabir; Kadori Haidar; Sutrisno; Muhammad Arya Dwiki Ressa Adriani (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The advancement of financial technology has encouraged Islamic boarding schools to implement digital transaction systems to improve the effectiveness of cooperative services. This study aims to analyze the ease of use of the student digital card and identify the supporting and inhibiting factors affecting its implementation at Hidsam Mart Cooperative, Hidayatullah Islamic Boarding School, Samarinda. The study employed a descriptive qualitative approach using observation, semi-structured interviews, and documentation, with data analyzed through the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the student digital card is easy to understand, operate, access, and learn, thereby accelerating transaction processes, improving service efficiency, and supporting more systematic financial record-keeping. The main obstacles identified include technical disruptions, network limitations, and the absence of independent features for checking account balances and transaction histories. The novelty of this study lies in its specific analysis of the ease of use of student digital cards within the context of an Islamic boarding school cooperative by emphasizing user experience as the primary basis for evaluating the implementation of a digital transaction system. The findings are expected to serve as a reference for the development of digital transaction services in Islamic boarding school environments.